Childhood Vitamin A Capsule Supplementation Coverage in Nigeria: A Multilevel Analysis of Geographic and Socioeconomic Inequities - Olatunde Aremu; Stephen Lawoko; Koustuv Dalal (The Scientific World Journal)
Vitamin A deficiency (VAD) is a huge public health burden among preschool-aged children in sub-Saharan Africa, and is associated with a high level of susceptibility to infectious diseases and pediatric blindness. We examined the Nigerian national vitamin A capsule (VAC) supplementation program, a short-term cost-effective intervention for prevention of VAD-associated morbidity for equity in terms of socioeconomic and geographic coverage. Using the most current, nationally representative data from the 2008 Nigerian Demographic and Health Survey, we applied multilevel regression analysis on 19,555 children nested within 888 communities across the six regions of Nigeria. The results indicate that there was variability in uptake of VAC supplement among the children, which could be attributed to several characteristics at individual, household, and community levels. Individual-level characteristics, such as maternal occupation, were shown to be associated with receipt of VAC supplement. The results also reveal that household wealth status is the only household-level characteristic that is significantly associated with receipt of VAC, while neighborhood socioeconomic disadvantage and geographic location were the community-level characteristics that determined receipt of VAC. The findings from this study have shown that both individual and contextual socioeconomic status, together with geographic location, is important for uptake of VAC. These findings underscore the need to accord the VAC supplementation program the much needed priority with focus on characteristics of neighborhoods (communities), in addition to individual-level characteristics.